First operations with caesium of the negative ion source SPIDER. (1st August 2022) - Sartori, E.; Agostini, M.; Barbisan, M.; Bigi, M.; Boldrin, M.; Brombin, M.; Casagrande, R.; Dal Bello, S.; Dan, M.; Duteil, B.P.; Fadone, M.; Grando, L.; et al.
Abstract: The negative-ion based neutral beam injector for heating and current drive of the ITER plasma (ITER HNB) is under development, at present focusing on the optimization of the full-scale plasma source in the SPIDER test stand. The production of H − or D − ions in the ion source is based on the low work function surfaces obtained by caesium evaporation. This paper describes the caesium conditioning procedure and the corresponding beam performances during the first operation of SPIDER with caesium. Technical solutions to overcome present limitations of the test stand are described. The influence of source parameters on the caesium effectiveness was investigated in short beam pulse operation; with total radio-frequency (RF) power of 400 kW and filling pressure below 0.4 Pa, and a limited number of extraction apertures, a negative ion current density of about 200 A m −2 was extracted in hydrogen, with beam energy lower than 60 keV. Beam optics and beam uniformity were assessed thanks to the acceleration of isolated ion beamlets. A possible procedure to accelerate a uniform beam was demonstrated at low RF power. The results obtained in this first investigation provided key indications on the operation of one of the largest existing sources of accelerated negative hydrogen-like ions.